Promotion Strategies And Product Innovation As Determinants Of MSME Income: A Sharia Marketing Approach (Case Study In Kopelma Darussalam) - Putriana, Devi; Amanatillah, Dara; Zulhilmi, Muhammad (JIMEBIS: Scientific Journal of Students Islamic Economics and Business, 2025)
Micro, Small and Medium Enterprises (MSMEs) have an important and strategic role for economic growth in Indonesia. The existence of MSMEs has the potential to increase income for business actors by implementing the latest promotional strategies and innovations that can provide innovation in business. Based on sharia marketing, promotions must be based on sharia compliance, which reflects the truth, justice and honesty of society, while product innovation is very important to carry out in the hope of maintaining the beneficial value of a particular product for consumers. This research aims to determine the influence of promotional strategies and product innovation on the income of MSMEs in Kopelma Darussalam. This research uses a quantitative method with an associative approach through distributing questionnaires using Roscoe, the data analysis method used in this research is the classical assumption test, multiple linear regression test and hypothesis testing using SPSS 22 software. The results of the research show that, partially and simultaneously, promotional strategy and product innovation variables have a significant effect on the income of MSME traders in Kopelma Darussalam.